2014
DOI: 10.1016/j.seizure.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of oxcarbazepine for treatment of refractory status epilepticus

Abstract: OXC could be used for refractory SE under close electrolyte monitoring when standard agents fail or are unsuitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…45 Use of oral oxcarbazepine in SE was reported in 13 patients with a median treatment latency of 81 hours. 46 Oxcarbazepine was the last drug in eight patients (62%); however, hyponatremia was seen in three of these individuals. 46 With regard to treatment-emergent adverse effects, our study contradicts the results reported by several other authors [27][28][29][30] who did not observe any adverse effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…45 Use of oral oxcarbazepine in SE was reported in 13 patients with a median treatment latency of 81 hours. 46 Oxcarbazepine was the last drug in eight patients (62%); however, hyponatremia was seen in three of these individuals. 46 With regard to treatment-emergent adverse effects, our study contradicts the results reported by several other authors [27][28][29][30] who did not observe any adverse effects.…”
Section: Discussionmentioning
confidence: 98%
“…46 Oxcarbazepine was the last drug in eight patients (62%); however, hyponatremia was seen in three of these individuals. 46 With regard to treatment-emergent adverse effects, our study contradicts the results reported by several other authors [27][28][29][30] who did not observe any adverse effects. In our study, hyperammonemia was present in 38 patients (35.8%), with a trend toward higher levels of ammonia in patients who received concurrent treatment with VPA and PB.…”
Section: Discussionmentioning
confidence: 98%
“…Both carbamazepine and oxcarbazepine (a derivate of the former) are known to cause hyponatremia with an occurrence of 4.8-31.3% and 0.14-73.3%, respectively [7,[13][14][15][16][17][18]. In our study, chronic use of oxcarbazepine was associated with the highest risk of hospitalization due to hyponatremia.…”
Section: Discussionmentioning
confidence: 46%
“…There is approximately a 25-30% chance of cross-reactivity between carbamazepine and oxcarbazepine. Number of cases of hyponatremia have been recorded with this treatment and with greater strength of association [49,84,90,92,98,99].…”
Section: Oxcarbazepinementioning
confidence: 99%